2017
DOI: 10.1016/j.joca.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of subchondral bone properties and changes in development of load-induced osteoarthritis in mice

Abstract: Objective Animal models recapitulating post-traumatic osteoarthritis (OA) suggest that subchondral bone (SCB) properties and remodeling may play major roles in disease initiation and progression. Thus, we investigated the role of SCB properties and its effects on load-induced OA progression by applying a tibial loading model on two distinct mouse strains treated with alendronate (ALN). Design Cyclic compression was applied to the left tibia of 26-week-old male C57Bl/6 (B6, low bone mass) and FVB (high bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 44 publications
6
60
0
Order By: Relevance
“…Previous studies have reported a higher average Tb.N and Tb.Th, which contributed to sclerotic changes in subchondral bone of advanced OA . In fact, the hypothesis that changes in subchondral bone might affect OA development is commonly acknowledged . Radin and Rose had originally proposed that densification of subchondral bone might lead to increased stiffness, thereby introducing adverse stress concentrations and sequential damage to articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a higher average Tb.N and Tb.Th, which contributed to sclerotic changes in subchondral bone of advanced OA . In fact, the hypothesis that changes in subchondral bone might affect OA development is commonly acknowledged . Radin and Rose had originally proposed that densification of subchondral bone might lead to increased stiffness, thereby introducing adverse stress concentrations and sequential damage to articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7) In fact, the hypothesis that changes in subchondral bone might affect OA development is commonly acknowledged. (4,9,(33)(34)(35)(36) Radin and Rose (37) had originally proposed that densification of subchondral bone might lead to increased stiffness, thereby introducing adverse stress concentrations and sequential damage to articular cartilage. Clinically, OP is another recognized factor that causes subchondral bone alterations in the functional unit of cartilage and subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly characterized by cartilage lesions, subchondral bone sclerosis and aseptic inflammation of the synovium (2). Previous studies have identified that the pathogenesis of osteoarthritis (OA) is initially caused by structural modification in the subchondral bone in response to changes in the mechanical environment (3)(4)(5). It has also been reported that subchondral bone of OA shows dysregulated bone modified by osteoblast and osteoclast activity (6), finally resulting in the formation of sclerosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo animal and in vitro tissue explant models have demonstrated that increased joint translation, contact stress, and impact force can lead to cartilage degeneration . But, the question remains—how are the applied forces and system boundary conditions related to the loading conditions experienced by the human knee joint after partial meniscectomy?…”
Section: Mechanical Predictors Of the Response To Partial Meniscectomymentioning
confidence: 99%